Implementasi Superenkripsi Dsa dan Aes 128 Bit Dalam Pengamanan File Surat Digital - Nuraeni, Fitri; Amrulloh, Muhammad Fawaz; Mulyani, Asri; Kurniadi, Dede (Institut Teknologi Garut, 2025)
Digital signatures are important for companies to overcome distance and time constraints. Therefore, a digital signature system is needed that is not only efficient but also has a high level of security to prevent data falsification or document legality. This research contributes to improving data security and integrity by implementing DSA and AES 128 Bit superencryption in the “Paperless Room” Digital Signature application. The implementation of the technology used is such as ReactJS, NodeJS, NextJS, cryptography modules in JavaScript, and PostgreSQL databases. Evaluation is done through penetration testing and measurement of encryption and decryption performance. The results show that this superencryption successfully improves efficiency and security, with an average encryption time of 165.67 ms and decryption of 98.17 ms, as well as an entropy value of 6.2837 which reflects a high level of security. In comparison, using DSA alone requires a longer encryption time of 242.97 ms and decryption of 312.83 ms, with a lower entropy of 4.8663. These findings confirm that DSA and AES-128 superencryption offer an optimal combination of efficiency and security for securing digital mail files in an enterprise environment.